Migracje międzynarodowe ludności po kryzysie 2008 r. - Wachowska, Małgorzata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The purpose of this chapter is to determine the effects of the 2008 crisis on the directions and nature of international human migration. In order to achieve this aim, the study has been divided into two main parts. The first one is devoted to selected major theories in migration while the second one is focused on the statistics of international migration flows, their evolution before and after 2008. The critical review of theoretical literature along with data analysis allows a better explanation of the impact of the crisis on the dynamics and directions of migration. The main conclusion of the research is that the crisis of 2008 strengthened the long-established trends in international migration rather than changed them. Any “abnormalities” observed after 2008 have only been insignificant and often of a short-term nature.
Keywords: highly skilled migration; inventor migration; international human migration; migration theories